Modification of Attenuation Rate in Range Normalization of Echo Levels for Obtaining Frequency-dependent Intensity Data from 0.6MHz and 1.0MHz Devices - Poerbandono, R.; Suprijo, Totok (ITB Journal Publisher, LPPM ITB, 2013)
This investigation aims to propose an attenuation rate for range normalization of echo amplitudes recorded by an acoustic backscattering instrument working at a frequency of 1.0 MHz. The intention of the use of such an attenuation rate is to obtain equal echo levels when using a device from the same family of products with a different working frequency, i.e. a 0.6 MHz instrument, at an identical site. This work is based on a field experiment with a 1.0 MHz Acoustic Wave and Current (AWAC) profiler and a 0.6 MHz Aquadopp profiler. Both profilers were deployed upward, side-by-side in the Semak Daun reef lagoon, Seribu Islands, Java Sea, Indonesia. It was found that the proposed attenuation rate for the 1.0 MHz instrument was one-order magnitude higher with respect to the one used for the 0.6 MHz instrument, and logarithmically depth dependent. The proposed attenuation rate for the 1.0 MHz AWAC is â7.925log(R) + 8.551, with R is the slant range from the transducers to the measured layer. Accordingly, the overall agreement between the 1.0 MHz AWAC echo amplitude and the one recorded by the 0.6 MHz Aquadopp was improved by 18dB, which is quite significant considering that the average echo amplitude discrepancy recorded by each transducer was 2.4dB.